Reliable and Effective Fault Diagnosis/Tolerance Technique Using Enhanced Distorted Current-Voltage SVPWM Method for Multilevel Inverters - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Industry Applications, 2024)
Faults are a common issue affecting the reliability of power conversion systems. They can occur in any switching device of a power converter. Open circuit faults are one of the most common types of faults, and their early detection and tolerance are crucial to prevent severe effects on the system. In this article, an enhanced distorted current-voltage space vector pulse-width modulation (SVPWM) method that can effectively detect and tolerate different open circuit faults in multilevel converters is presented and illustrated. In the proposed method, changes in the output current and DC link voltage are detected first, and a specific look-up table is then generated for accurate detection of the faulty device. Subsequently, after the fault is detected, a modified SVPWM fault tolerance strategy is applied to mitigate the effects of the fault and restore the healthy operation of the system. The effectiveness of the proposed method is verified through simulation and experimental results.
Keywords: Circuit faults; Distorted currents; Fault- tolerant systems; Faults detection; Faults diagnosis; Multilevel inverter; Multilevels; Open-circuit fault; Space vector pulse width modulation; Space vector pulse-width modulation modulation; Fault detection; fault tolerance; multilevel inverters; Open Circuit Faults; SVPWM Modulation